Antimicrobial Susceptibilities of Enterobacteriaceae in Community-Acquired Urinary Tract Infections during a 5-year Period: A Single Hospital Study in Korea - Park, Jin Ju; Seo, Yu Bin; Lee, Jacob (Infection & chemotherapy, 2017)
Through investigating antimicrobial susceptibility patterns of Enterobacteriaceae in community-acquired urinary tract infection (CA-UTI), we provide basic evidence for the use of empirical antibiotics in CA-UTI. We retrospectively reviewed the medical records of patients over the age of 19 years who visited a hospital in Seoul between January 2012 and December 2016 for a CA-UTI. Urine cultures were used to identify causative organisms. We investigated extended-spectrum β-lactamase (ESBL) production and the antimicrobial susceptibility of Enterobactereiaceae. We evaluated recommended empirical antibiotics numerically by calculating the syndrome-specific likelihood of inadequate therapy (LIT) for the last 2 years (interpretation of the LIT A value: 1 out of A people is likely to receive inadequate empirical antibiotics). Urine cultures were performed in 1,605 out of 2,208 patients who were diagnosed with CA-UTI, and causative pathogens were identified in 1,134 (70.7%) cases. There were 998 (88.0%) cases of Enterobacteriaceae and Escherichia coli was the most common pathogen, accounting for 80.3% of cases (911 cases). The overall resistance rates to trimethoprim-sulfamethoxazole, fluoroquinolones, and cefotaxime were 31.7%, 23.2%, and 13.5%, respectively. There were 128 (10.8%) cases of ESBL-producing Entererobacteriaceae with an increasing but non-significant trend (P = 0.255). The LIT for CA-UTI in the past two years was highest for ertapenem and imipenem. Fluoroquinolones ranked 11th, with a LIT of 8.2, and cefotaxime ranked higher, at 10.5. In ESBL-producing Enterobacteriaceae, except for carbapenems, amikacin and piperacillin-tazobactam showed the highest susceptibility rates at 99.2% and 94.3%, respectively. Empiric treatment with fluoroquinolones in CA-UTI should be carefully considered, given the high resistance rate. The proportion of ESBL-producing Entererobacteriaceae in CA-UTI has increased to a high level in Korea. Amikacin and piperacillin-tazobactam could be considered for empiric treatment in patients at risk for ESBL-producing Entererobacteriaceae when considering alternatives to carbapenems.